2019
DOI: 10.3390/rs11050477
|View full text |Cite
|
Sign up to set email alerts
|

Object-Based Classification of Forest Disturbance Types in the Conterminous United States

Abstract: Forest ecosystems provide critical ecosystem goods and services, and any disturbance-induced changes can have cascading impacts on natural processes and human socioeconomic systems. Forest disturbance frequency, intensity, and spatial and temporal scale can be altered by changes in climate and human activity, but without baseline forest disturbance data, it is impossible to quantify the magnitude and extent of these changes. Methodologies for quantifying forest cover change have been developed at the regional-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 75 publications
1
18
0
Order By: Relevance
“…The overall accuracy of 89% across districts is in line with accuracies reported in many of those studies. Using the Landsat archive, high overall accuracies have been reported for stand-replacing forest disturbance classifications, for example 93% [71], 88% [72], 90% [73], and 88% [74]. However, studies that included non-stand replacing disturbances in the classification reported lower overall accuracies; 75% [73] and 80% [75], likely because subtle forest changes do not tend to display a clear spectral change that can be linked to a change in land cover class [76,77].…”
Section: Discussionmentioning
confidence: 99%
“…The overall accuracy of 89% across districts is in line with accuracies reported in many of those studies. Using the Landsat archive, high overall accuracies have been reported for stand-replacing forest disturbance classifications, for example 93% [71], 88% [72], 90% [73], and 88% [74]. However, studies that included non-stand replacing disturbances in the classification reported lower overall accuracies; 75% [73] and 80% [75], likely because subtle forest changes do not tend to display a clear spectral change that can be linked to a change in land cover class [76,77].…”
Section: Discussionmentioning
confidence: 99%
“…Also, the geomorphological indices seemed to play a less important role. They improved the total performance of the models by bringing non-redundant information to the models as earlier found by Huo et al [51] and Oeser et al [26]. The unique aspect of this study lies in the use of topography information which mitigates the relief effect on the spectral bands reflectance [33].…”
Section: Adjustment Of Models and Importance Of Variablesmentioning
confidence: 87%
“…However, this information is very important, for example, to specifically assess the amount of damage caused by bark beetle infestation [11]. Previous studies have already tried to discriminate different categories of change by directly using various disturbance metrics or by using those metrics as input data for machine learning algorithms (e.g., Random Forest) [20,[77][78][79][80]. First tests based on our data suggest that there are specific patterns both in the single pixel courses as well as in the FDD maps that could help to categorize disturbances by the cause of disturbance.…”
Section: Recommendationsmentioning
confidence: 99%